Automatic temperature control of flute in paper corrugated box manufacturing machine - et. al., Dr Bharat Chede, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Paper corrugate boxes are widely and extensively used for packing of industrial and domestic item. There are various kinds, depending on the item to be package, size, thickness, and strengths. Cardboard pass through flutes at high temperature at 180-250 degree Celsius. Due to continue running of roller, roller temperature increase above 270 degrees Celsius and leads to halt production for some time to cool down rollers. In this paper, studying feasible option to overcome overheating problem..